Virtualization with Microsoft Virtual Server 2005 - Dittner, Rogier (Syngress, 2006)
A virtual evolution in IT shops large and small has begun. Microsoft's Virtal Server is the enterprise tool to free an infrastructure from its physical limitations providing the transformation into a virtual environment--this book shows you how. This book will detail the default and custom installation of Microsoft's Virtual Server 2005, as well as basic and advanced virtual machine configurations. It will also discuss the requirements for a server virtualization and consolidation project and the cost savings surrounding such an effort. Furthermore, the book will provide a thorough understanding of the benefits of a virtual infrastructure and a comprehensive examination of how Virtual Server can ease administration and lower overall IT costs. Lastly, the book delivers a thorough understanding of the virtual evolution which is underway in many IT organizations and how the reader will benefit from shifting from the physical to a virtual world. * Examines in detail the default and custom installation of Microsoft's Virtual Server 2005 * Addresses th important topics of server requirements and the cost implications involved * Looks at addressing IT costs and the benefits to the organisation.